(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
urpose: The purpose of this study was to investigate the relationship between nurse factors and the quality of nursing services provided to orthopedic patients in hospitals in Indonesia. This cross-sectional study was conducted from July to September 2022. Questionnaires were administered to 236 nurses and 236 patients in 10 orthopedic hospitals in West Java Province, Indonesia. Using univariate analysis and chi-square analysis, it was found that competence and skills were significantly related to nursing service quality. Meanwhile, age, gender, educational level, length of employment, and knowledge were not significantly related. Even though knowledge had no bearing on service quality in this research, mature knowledge is needed to meet competency and skill requirements for improving service quality at levels ranging from mild to complex.